Growth and non-critical phase-matching frequency conversion properties of LaxY1−xCOB crystals. Issue 33 (14th July 2016) - Qi, Hongwei; Wang, Fang; Chai, Xiangxu; Wang, Zhengping; Yu, Fapeng; Liu, Yanqing; Zhao, Xian; Xu, Xinguang
Abstract : A new series of nonlinear optical crystals La x Y1− x COB with multiple components were grown and used for the NCPM frequency conversions. Abstract : A new series of nonlinear optical crystals La x Y1− x Ca4 O(BO3 )3 (La x Y1− x COB) with multiple components were grown by using the traditional Czochralski pulling method. X-ray powder diffraction and single-crystal X-ray diffraction experimental results proved that all these crystals formed in the La x Y1− x COB solid solution state with a monoclinic structure of space group Cm . The optical birefringence was found to be adjustable by changing the compositional parameter x for the La x Y1− x COB crystals. Taking advantage of the optical parametric oscillator laser, the non-critical phase-matching (NCPM) second-harmonic-generation (SHG) and third-harmonic-generation (THG) wavelengths along the Y -axis were determined at ambient temperature. In addition, the relationships between and among the optical birefringence, NCPM wavelength and crystal structure were discussed, and the NCPM SHG and THG of the 1064 nm laser were further achieved from the La0.120 Y0.880 COB and La0.140 Y0.860 COB crystals by adjusting the temperature, respectively. Using a 1064 nm Nd:YAG laser as the fundamental light source, the angular acceptance, temperature acceptance, and optical conversion efficiencies were determined and found to be on the order of 107.6 mrad, 18.3 °C and 48.8% for SHG of the La0.120 Y0.880 COB crystal, respectively, and 126.8 mrad, 68.6 mrad, 10.6 °C and 32.4% for THG of the La0.140 Y0.860 COB crystal, respectively. It is demonstrated that La x Y1− x COB is a promising NLO crystal for NCPM frequency conversion applications in the visible and ultraviolet spectral regions.